Analisis Dampak Ekonomi dan Sosial Pembangunan Tol terhadap Pasar Bengkel di Perbaungan - Romauli Situmorang; Mira Susila Warni; Sri Muthia Hasan; Tamim Hasyimi; Rohani Rohani (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2025)
The development of road infrastructure undoubtedly has a detrimental impact on society. The Serdang Bedagai Regency government's infrastructure development is an example of how something that is deemed beneficial by some always has a detrimental impact on others. This research intends to examine the influence of the building and operation of the Medan-Tebing Tinggi Toll Road on the socio-economic conditions of the community in the Pasar Bengkel area, Bengkel Village, Perbaungan District, Serdang Bedagai Regency. This study employed a qualitative descriptive case study methodology and gathered information via literature review, in-depth interviews, and direct observation. This study, which was carried out on February 15, 2025, involved three resource people who worked in Pasar Bengkel stores. According to the research, the toll road's construction and operation have a significant impact on Pasar Bengkel businesses. Prior to the toll road, Pasar Bengkel's average monthly income ranged from Rp10 million to Rp50 million, which suggests that local traders were enjoying rather favorable economic conditions. Around 80% of traders, however, reported a more than 50% decrease in income when the toll road opened, with the majority only making IDR3 million to IDR10 million a month.